Seizing market shaping opportunities for vaccine cold chain equipment. Issue 17 (19th April 2017) - Azimi, Tara; Franzel, Lauren; Probst, Nina
Graphical abstract: Abstract: Gavi, the Vaccine Alliance, supports immunisation programmes in eligible countries to reach children with lifesaving vaccines. Dramatic improvement in the scale and performance of current cold chain systems is required to extend the reach of immunisation services - especially for children living in remote locations - to advance progress towards full vaccine coverage. Achieving these improvements will require a healthier market for cold chain equipment where the products meet user needs, are sustainably priced, and are available in sufficient quantities to meet demand. Yet evidence suggests that the cold chain market has suffered from several failures including limited demand visibility, fragmented procurement, and insufficient information exchange between manufacturers and buyers on needs and equipment performance. One of Gavi's strategic goals is to shape markets for vaccines and other immunisation products, including cold chain equipment and in 2015, Gavi created a new mechanism – the Cold Chain Equipment (CCE) Optimisation Platform - to strengthen country cold chain systems by offering financial support and incentives for higher performing CCE. The main objective of the CCE Platform is to get more equipment that is efficient, sustainable, and better performing deployed to every health facility where it is required at an affordable price. To achieve these objectives, Gavi is putting in place tested market shaping approaches and tools adapted for the CCE market: the development of market strategies or 'roadmaps'; improvement of product performance through the development of target product profiles (TPPs); strategic engagement with CCE manufacturers and countries to enhance information sharing; and tailoring procurement tactics to the CCE market. These approaches and tools will allow for increased demand and supply of higher-performing, cost-effective and quality products. By strengthening immunisation systems with improved cold chain equipment, Gavi countries can begin to address the underlying problems limiting vaccine availability and improve the coverage and equity of vaccines.